The New Challenges of Populist Discourses in Romance Speaking Countries - Roitman, Malin; Bernal, María; Premat, Christophe; Sullet-Nylander, Francoise (Stockholm Studies in Romance Languages, 2023)
The aim of this volume is to identify, explore and compare expressions of populism in the Romance-speaking part of the world. The volume includes studies from different academic disciplines such as discourse analysis, cultural and media studies. Populist discourses are generally characterized by a deep polarization of positions and a disproportionate reliance on accusations. Populist discourses frequently reinforce existing antagonisms and undermine the traditional political argumentative style, based on the factual confrontation of opinions in the public space. Populist leaders often present themselves as the unfettered spokespersons of the people with whom they form a community of "us" in the struggle against "them". This accords with the strong polarization mentioned earlier. The rise of populist discourses in many countries over the past decades could be due to changes in political communication. The constant and overwhelming dissemination of information in all types of media, the consequent relativization of truth, as well as a less clear political division on a left-right scale, could favor political alternatives based on personality and the highly polarized messages we see today. The question of how to reach voters in today's media buzz is a much bigger question today than it was a few decades ago, and the exposure of faces and comments has increased exponentially, which in itself can promote a certain kind of politicians. In fact, there is a strong emphasis on the leadership of populist movements, which is also a recurring theme in this book, alongside the impact of the new media landscape on political discourses. In this light, some of the recurring themes in the thirteen studies included in the volume are the denunciation - by populist voices - of the corruption of the so-called elites as well as their inability to solve concrete political and economic problems. It is also about the escalation and reinforcement of populist discourses as an expression - an act - of extreme criticism, even hatred, against traditional political leaders. These populist voices are looking for scapegoats and claiming proximity to the people, represented in the discourse as an authentic and uniform group. Other recurring themes are the emphasis on traditional values, national symbols, ethnicity, and nostalgia for a bygone era, which are effective subjects for eliciting feelings and fostering a sense of togetherness. The interplay between some of these issues is explored in more detail in the book. The chapters of the book indeed show to what extent populist discourses introduce a system based on characteristics such as unilaterality, through the designation of a threat and/or a common enemy, and on the strong focus on the rejection of the legitimacy of the adversary.